Burnout among clinical and non-clinical academics during the implementation of remote teaching and learning due to COVID-19 Pandemic - Ayub, Izzudeen; Muhd Helmi, Muhd Alwi; Mohd Azhar, Nur Syuhada; Mohd fauzi, Nurul Fauwiza; Taib, Mai Nurul Ashikin; Sharifudin, Mohd Ariff (Universiti Putra Malaysia, 2022)
Introduction: The extent of burnout among clinical and non-clinical academics during the COVID-19 pandemic is not well gauged and necessitates further attention. This study was designed to determine the prevalence of burnout among academics in the International Islamic University Malaysia (IIUM), Kuantan campus, and the associated sociodemographic and occupational-related factors. Methods: We conducted a cross-sectional study between March and May 2021 using questionnaires adapted from Copenhagen Burnout Inventory and General Stressor Questionnaire at the IIUM, Kuantan campus. Results: 57 clinical and 93 non-clinical academics responded to the survey. The prevalence of significant burnout was 49%. Compared to non-clinical academics, clinical academics had a significantly higher proportion of burnout with a p-value of <0.001, particularly in work-related, student-related, and superior-related burnout domains, with a p-value of 0.004, <0.001, and 0.006, respectively. Factors significantly associated with burnout among our cohort were clinical work, chronic illness, and gender, each with an odds ratio of 2.72 (95% CI = 1.01,7.34), 2.81 (95% CI = 1.14, 6.92), and 4.86 (95% CI = 2.15, 10.9). Conclusion: Burnout was highly prevalent among academics in the IIUM Kuantan campus, particularly among clinical academics during the COVID-19 pandemic and the implementation of remote teaching and learning policy.